DO ISLAMIC FINANCING CONTRACTS ENHANCE BANK PROFITABILITY? EVIDENCE FROM THE MEDIATING ROLE OF FINTECH ADOPTION IN INDONESIA - Erwin Saputra Siregar; Fitri Sagantha; M Taufik Ridho; Rohaiza Kamis; Resa Iswara (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2026)
The present study investigates direct and indirect impacts of six financing instruments including murabaha, mudaraba, musyarakah, ijarah, istishna and qardh of Islamic finance on the profitability of Indonesia's Islamic banks, measured through Return On Assets (ROA), where fintech adoption becomes the mediator. This study adopted quantitative explanation method, where secondary monthly times series data collected from the statistics of Islamic Banking reported by the Financial Services Authority (OJK) for the years 2015 - 2024 were used. The structural relationship between the variables was tested with path analysis, supported by Sobel test and bootstrapping with 5,000 samples to test mediation effect. The results found that mudaraba financing instrument had the highest positive impact on fintech adoption, showing higher association with financial innovation in comparison to other Islamic financing instruments. Digital transformation expenditure, which represents fintech adoption, significantly negatively impacts ROA; therefore, technology investments put immediate pressure on the profitability of the bank. Moreover, none of the Islamic financing instruments had a direct effect on ROA, but mudaraba financing instrument yielded a significant indirect effect on ROA through fintech adoption. These findings suggest that Indonesian Islamic banks remain in the early stage of digital transformation, highlighting the need for more efficient digital integration and supportive regulatory frameworks to achieve sustainable long-term profitability.